2003
DOI: 10.1359/jbmr.2003.18.7.1217
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Calcium and Phosphorus Ratio Regulates Bone Mineralization and Turnover in Vitamin D Receptor Knockout Mice by Affecting Intestinal Calcium and Phosphorus Absorption

Abstract: The effects of the dietary Ca and P ratio, independent of any vitamin D effects, on bone mineralization and turnover was examined in 60 VDRKO mice fed different Ca/P ratio diets. High dietary Ca/P ratio promoted bone mineralization and turnover with adequate intestinal Ca and P transports in VDRKO mice. Introduction:To clarify the effects of the dietary calcium (Ca) and phosphorus (P) ratio (Ca/P ratio) on bone mineralization and turnover in null-vitamin D signal condition, vitamin D receptor knockout (VDRKO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 25 publications
2
82
0
1
Order By: Relevance
“…The dietary Ca to P ratio regulates bone mineralization and turnover by affecting the intestinal Ca and P transports in mice (Masuyama et al, 2003). The imbalance between Ca and P also impaired bone mineralization of pigs (Létourneau-Montminy et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The dietary Ca to P ratio regulates bone mineralization and turnover by affecting the intestinal Ca and P transports in mice (Masuyama et al, 2003). The imbalance between Ca and P also impaired bone mineralization of pigs (Létourneau-Montminy et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…13) In this present study, we did not change the dietary Ca level in the dietary groups and maintained an adequate level in the diets (0.5%). However, a decreased dietary P level led to an increased dietary Ca/P ratio, and then to increased Ca absorption and bone mineralization in adult female rats.…”
mentioning
confidence: 75%
“…Therefore, the low-P diet enhanced Ca absorption which was effective for bone mineralization in adult female rats, as well as in vitamin D receptor knockout male mice in our previous study. 13) In spite of the enhanced bone mineralization, the serum P concentration was lower in the rats fed the low-P diet than in those fed the control diet. Similarly to Ca, P is one of the important minerals for bone constitution.…”
mentioning
confidence: 90%
“…The active metabolite has many functions related to Ca regulation and bone metabolism, including intestinal Ca and P absorption, Ca mobilization in the bone, and resorption of P and Ca in the renal tubular cells (Deluca 2004;Jones et al 1998;Lips 2006). Although vitamin D interacts with PTH (Deluca 2004;Jones et al 1998), hypovitaminosis D does not influence PTH under sufficient serum levels of Ca (Dabbagh et al 1989;Kollenkirchen et al 1991), and many researchers (Fox 1992;Lee et al 1991;Masuyama et al 2003) have reported a vitamin D-independent Ca homeostasis system. Therefore, hypovitaminosis D alone might not affect Ca homeostasis and bone remodeling owing to the vitamin D-independent system in the present experiment.…”
Section: Discussionmentioning
confidence: 99%